فقہ حنفی کے اصول اجتہاد :المبسوط امام محمد کی روشنی میں تجزیاتی و اطلاقی مطالعہ : Principles of Ijtihad in Hanafi Jurisprudence: An Analytical and Applied Study in the Light of Al-Mabusut Imam Muhammad - Akhter, Ayaz; Hasib, Muhammad (MEI, 2023)
Imam Muhammad has a high position in the world of knowledge. Imam Muhammad has a unique personality in the field of Jurisprudence. No one has worked in this manner and style before the manner in which he codification of Jurisprudence. Imam Muhammad's books are among the basic books of Hanafi religion. The principles of Imam Muhammad's ijtihad are derived from the basic sources of Islamic law, which purpose is to expand the scope of Islamic law. Imam Muhammad has adopted the following principles of Ijtihad : The Holy Quran, Sunnah of the Messenger of Allah, proverbs of the Sahabi, Ijmaa (consensus), Qiyas (measure), Isthisan, Istishab (escort), custom and habit, previous shari'ah, Barrier sources and expediency. These principles of Ijtihad of Imam Muhammad are overall others agree with the principles of the jurists. Imam Muhammad prefers the saying of the Sahabi over consensus and the text over Qiyas. Imam Muhammad has adopted Appreciation and Alias more than other jurists in codification of jurisprudence. Imam Muhammad in this book there are examples of this. Imam Muhammad takes the same orders from previous Sharia's which are evidenced in the Shariah of Muhammad. Imam Muhammad while living in the realm of the Sharia has described the aspects of the Muslim Ummah that are easy and easy. Imam Muhammad is convinced of principles rather than personalism. Examples of which can be seen in the book of "Al Hujjah tu ala Ahl-Madinah" and other books. Imam Muhammad's jurisprudential arguments are proof of his knowledge.